A SYSTEM OF EXERCISES TO IMPROVE STUDENTS' MONOLOGUE SPEECH - Niyazova Nasiba Zhurabekovna (American Journals Publishing, 2024)
The article presents material on a purposeful system of work carried out in a functional and stylistic aspect to improve the oral and written speech of students. Based on the set goal, as well as depending on the tasks to be solved at each stage, a system of exercises can be proposed. So, at the first stage, analytical exercises are mostly performed, at the second — analytical-constructive and constructive, and at the third – only constructive.
Keywords: Oral and written speech, speech utterance, monologue speech, the principle of conscious assimilation of knowledge about language